2012
DOI: 10.1089/jop.2011.0127
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single Glaucoma Medication in Combined Latanoprost and Timolol XE Therapy in Patients with Open-Angle Glaucoma and Ocular Hypertension: A Discontinuation Study

Abstract: There was a significant increase in IOP from discontinuation of timolol XE and latanoprost. The hypotensive effect of latanoprost in the combined drug therapy is significantly greater compared with timolol XE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Of the five articles included in the meta-analysis, all except Kobayashi [ 19 ] showed a return to baseline IOP following a washout of 3 or 4 weeks. Participants in the study by Kobayashi [ 19 ] continued on their other intraocular medications, while the other studies had participants discontinue their previous drops prior to the start of each study [ 18 22 ]. Stewart et al were the first to identify that there may be a variation in the time to return to baseline IOP following washout in individuals being treated with latanoprost.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the five articles included in the meta-analysis, all except Kobayashi [ 19 ] showed a return to baseline IOP following a washout of 3 or 4 weeks. Participants in the study by Kobayashi [ 19 ] continued on their other intraocular medications, while the other studies had participants discontinue their previous drops prior to the start of each study [ 18 22 ]. Stewart et al were the first to identify that there may be a variation in the time to return to baseline IOP following washout in individuals being treated with latanoprost.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of existing literature demonstrated that after washout, IOP returned to baseline values, with a maximum of 17% IOP reduction (IOPR%) from baseline occurring at 4-weeks after washout. Of the eight articles which met the study criteria, the difference between baseline IOP (pretreatment) and postwashout IOP was statistically significant in only 3 studies [ 18 , 19 , 23 ]. A 4-week discontinuation of latanoprost in patients who had remained on beta-blockers and brinzolamide did not have an expected increase of 25–33% of pretreatment IOP, but only a 15.4% of baseline IOP increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations